2017
DOI: 10.1016/j.jcis.2017.01.117
|View full text |Cite
|
Sign up to set email alerts
|

Removal of sodium dodecyl sulfate surfactant from aqueous dispersions of single-wall carbon nanotubes

Abstract: A reagent-based treatment method was developed for the removal of sodium dodecyl sulfate (SDS) from aqueous dispersions of single-wall carbon nanotubes (SWCNTs). Based on a survey of various reagents, organic solvents emerged as the most effective at interrupting the SDS:SWCNT interaction without producing deleterious side reactions or causing precipitation of the surfactant. Specifically, treatment with acetone or acetonitrile allows for the facile isolation of SWCNTs with near complete removal of SDS through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Concurrently, any capping agents at FLP surfaces should be readily removable to exploit the intrinsic surface characteristics of FLPs . In this regard, vacuum filtration of aqueous dispersions, followed by thorough water rinsing, was employed for highly pure FLP based films. , The absence of low angle peaks (4.54° and 6.8°) in XRD (Figure g) for P/CTAB films after filtration and water rinsing indicates that surfactants were mostly removed (Figure S17). Optical microscope (OM) and SEM images of the gas sensing devices confirm the high uniformity of FLP film, without significant roughness and voids (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, any capping agents at FLP surfaces should be readily removable to exploit the intrinsic surface characteristics of FLPs . In this regard, vacuum filtration of aqueous dispersions, followed by thorough water rinsing, was employed for highly pure FLP based films. , The absence of low angle peaks (4.54° and 6.8°) in XRD (Figure g) for P/CTAB films after filtration and water rinsing indicates that surfactants were mostly removed (Figure S17). Optical microscope (OM) and SEM images of the gas sensing devices confirm the high uniformity of FLP film, without significant roughness and voids (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…By mixing the solvent with good solubility in the surface, the interaction between SDS and SWNT is interrupted, and as a result, pure SWNTs can be separated. A study by Rossi et al confirmed that acetone and acetonitrile could separate SWNTs from SDS with high purity [ 120 ].…”
Section: Allyl Dextran-based Gelsmentioning
confidence: 99%
“…It is worth pointing out that these studies mostly involve sorting of SWCNTs through polymer/surfactant wrapping. The residual surfactants/polymer on the sidewalls of SWCNTs limits the full advantage of their unique properties . However, various strategies to remove the surfactants/polymer after separating the nanotubes are now being developed .…”
Section: Applications Of Sorted Carbon Nanotubesmentioning
confidence: 99%
“…The residual surfactants/polymer on the sidewalls of SWCNTs limits the full advantage of their unique properties . However, various strategies to remove the surfactants/polymer after separating the nanotubes are now being developed . Mohite's group, for example, have studied the influence of two wrapping polymers, namely PFO and PFO‐BPy, commonly used to sort (7,5) and (6,5) SWCNTs on the performance of a solar cell .…”
Section: Applications Of Sorted Carbon Nanotubesmentioning
confidence: 99%